Advancements in Surface Coatings and Inspection Technologies for Extending the Service Life of Concrete Structures in Marine Environments: A Critical Review - Taehwi Lee; Dongchan Kim; Sanghwan Cho; Min Ook Kim (Buildings)
Concrete structures in marine environments are subjected to severe conditions that significantly compromise their durability and service life. Exposure to chloride penetration, sulfate attack, and physical erosion accelerates deterioration, leading to extensive maintenance requirements and high associated costs. To address these challenges, significant advancements in surface coatings and inspection technologies have been developed to enhance the longevity of concrete structures. This review examines recent progress in protective surface coatings that mitigate environmental damage and explores state-of-the-art inspection techniques for assessing structural integrity. By providing a comprehensive analysis of innovative materials, coating applications, and non-destructive evaluation methods, this paper aims to equip researchers and industry professionals with effective strategies for preserving concrete infrastructure in marine environments.